Equity offering following cyberattacks - Liu, Xiaohui; Luo, Juan; Yawson, Alfred (Journal of Corporate Finance, 2025)
We investigate the impact of cyberattacks on a firm's equity issuance decisions. Our findings indicate that firms targeted by cyberattacks are less likely to pursue seasoned equity offerings (SEOs) afterward. This effect is more pronounced when the target firm has lower external financing needs and operates in a poor information environment. This result remains robust after addressing sample selection bias through propensity score matching and entropy balancing approaches. We attribute this reduction in SEO activities to reputation loss, investors' adverse selection, and the resulting higher equity financing costs. Furthermore, we demonstrate that the negative impact of cyberattacks on SEOs extends to industry peers. This spillover effect is stronger when the target firm suffers significant reputation loss, when the stock prices of peers closely correlate with those of the target firm, when peer firms possess a higher ex-ante cyber risk, and when they are more vulnerable to future cyberattacks.